Dynamic changes of the hemoglobin index during resuscitation in patients with out-of-hospital cardiopulmonary arrest due to freshwater drowning: A retrospective observational study - Tomoya Hirose (Elsevier, 2021)
Background: The hemoglobin index (HbI) represents the amount of hemoglobin, which reflects the regional tissue blood volume. The HbI is calculated by a regional oxygen saturation monitor. In freshwater drowning, inhaled water is immediately absorbed into the blood causing hemodilution. We hypothesized that this blood dilution could be observed in real time using HbI values in patients with out-of-hospital cardiac arrest (OHCA) due to freshwater drowning. Methods: In this single-center retrospective, observational study, we examined the HbI in patients with OHCA due to freshwater drowning from April 2015 to May 2020. Patients with OHCA due to hanging were selected as a control group. Results: Thirty-two patients in the freshwater drowning group and 21 in the control group were eligible for inclusion. In the freshwater drowning group, the HbI values in the return of spontaneous circulation (ROSC) group were significantly decreased in comparison to the non-ROSC group (−0.28 [IQR −0.55, −0.12] vs. −0.04 [IQR −0.16, 0.025]; p = 0.024). In the control group, the change of HbI during resuscitation in the ROSC and non-ROSC groups was not significantly different (0.11 [IQR −0.3525, 0.4225] vs. −0.02 [IQR −0.14, 0.605]; p = 0.8228). In each patient with ROSC in the freshwater drowning group, the HbI value after ROSC was significantly decreased in comparison to before ROSC (1.2±0.5 vs. 0.9±0.5]; p = 0.0156). In contrast, this difference was not observed in patients with an ROSC in the control group (3.7±1.3 vs. 3.8±1.4]; p = 0.7940). Conclusion: Blood dilution induced by freshwater drowning might be detected in real time using the HbI. To prove the validity of this research’s result, further prospective large study is needed.